Hantavirus antibody seroprevalence and risk factors among adults in West Kazakhstan, 2023 - Ulyana Gubareva; Ulyana Gubareva; Ulyana Gubareva; Roberta Horth; Roberta Horth; Dilyara Nabirova; Dilyara Nabirova; Nur Tukhanova; Nur Tukhanova; Elmira Utegenova; Elmira Utegenova; Zhanna Shapiyeva; et al. (Frontiers in Public Health)
BackgroundOrthohantaviruses (also known as hantaviruses) are pathogens, primarily transmitted by rodents, that can cause hemorrhagic fever with renal syndrome (HFRS). In endemic regions of Kazakhstan, no confirmed HFRS cases were detected between 2020 and 2022 raising concerns about detection. Estimate antibody seroprevalence for hantaviruses and identify associated risk factors among high-risk adults in western Kazakhstan in 2023.MethodsIn this cross-sectional study, adults were randomly sampled from public clinic registries in 14 villages in West Kazakhstan during June–July 2023. We interviewed 921 participants and collected serum samples which were tested for presence of hantavirus specific IgG antibodies using enzyme-linked immunosorbent assay (ELISA). Socio-demographic, clinical characteristics, and residential risk-factor data were self-reported. We assessed factors associated with seropositivity using multivariable Poisson regression, adjusting for key variables such as age and gender.ResultsAmong 921 participants, 63.0% were female, median age was 53 years, 72.0% resided in single houses and 38.0% reported encounters with rodents. Among 921 participants we found 3.1% (n = 28) hantavirus seroprevalence (95% confidence interval [CI]: 2.1–4.3). No seropositive participants had prior hospitalization or symptoms consistent with hantavirus. Three seronegative participants had previous hospitalization for hemorrhagic fever with renal syndrome. Over one-third (38%) of participants encountered rodents or droppings in the past year in their homes or workplaces. Higher seroprevalence was found among office occupational workers than unemployed people (prevalence ratio [PR]:7.3, 95%CI: 1.3–53.5), and among those who lived near ponds than those who did not (PR:11.5, 95%CI: 1.6–54.7).ConclusionOverall, the seroprevalence was low, but indicated some risk of infection among the adult population. Our results highlight potential occupational and residential risk factors for hantavirus infection in West Kazakhstan. Relevant public health interventions should include educating the population about promoting preventive practices, workplace hygiene, rodent control measures, and enhanced case diagnosis and management.